Rancang Bangun Bel Otomatis pada STIKOM Tunas Bangsa Berbasis Arduino dengan Output Suara - Fachrul Hasby; S Sumarno; Fitri Anggaini; Iin Parlina; Zulaini masruro Nasution (Bulletin of Computer Science Research, 2021)
The bell is certainly no stranger to the world of education. In general, the bell still uses human power to ring it. It is still rare in the world of education to use an automatic bell that can work alone according to the specified time in the teaching and learning process. The purpose of designing the automatic bell at STIKOM Tunas Bangsa Pematangsiantar is to simplify the work of picket officers and optimize the right time for the teaching and learning process. The work process of this tool is to input the predetermined class hours into the Arduino Uno Microcontroller using the C language in the Arduino IDE Software. After that the Microcontroller will read the schedule program for lessons that have been input into the Microcontroller. If the input program matches today's class time schedule, the bell will automatically issue the output in the form of an information notification sound. This tool also has a 16x2 Keypad Shield for manual setting in a matched test mode within the current exam time and automatically generates a notification sound output, where this automatic buzzer is fully controlled by the Arduino Uno Microcontroller command and the timing that has been set in the RTC ( Real Time Clock) as a time saver